First FRCA anatomy : mock papers - Budak, Matthew; Szewczyk-Bieda, Magdalena; White, Richard (London : JP Medical, 2013)
First FRCR Anatomy: Mock Papers offers up-to-date and comprehensive coverage of practice cases for trainees preparing for the First FRCR Anatomy exam. Fifteen complete mock papers are presented in exactly the same structure as the First FRCR Anatomy exam, enabling trainees to practice and improve exam technique. Featuring a wealth of practice cases covering all the key topics, this book is an essential revision tool to maximise chances of exam success. 300 high-quality images reflect the full breadth of topics encountered in the exam. 15 mock papers cover the full range of imaging modalities.
Includes index
Keywords: Anatomy; Radiology; Examination Questions